Survey on human-designated antiretroviral (ARV) drug residues in broiler chicken, domestic pigs, and animal feeds in, Tanzania - Kimera, Zuhura I.; Shimo, Peter; Balandya, Emmanuel C.; Matee, Mecky I. N.; Adams, Lisa V. (Springer Berlin Heidelberg, 2025)
BackgroundRecent reports have indicated the use of antiretroviral (ARV) drugs in animal production in neighboring Uganda, with further reports of use in several African countries. This cross-sectional survey was conducted in nine districts in Tanzania and involved screening for the presence of three first-line ARVs (lamivudine, nevirapine, and efavirenz) residues in the muscle and blood of domestic pigs and broiler chickenss and in sampled animal feed and water. Residues were determined using liquid chromatography and mass spectrometry (LC–MS/MS). The method involved calibration of the lower limit of quantitation (LLOQ) and limit of detection (LOD). ARVs were detected and quantified using the multiple reaction monitoring (MRM) system.Results131 (66.8%) of the 196 samples of muscle, blood, and animal feed were found to contain lamivudine residues, with the highest concentration detected in domestic pig blood and muscle (7.58 mg/kg) and the lowest concentration (0.01 mg/kg) in broiler chicken feed. There was a significant relationship between the presence of lamivudine by sample type and sample origin (p = 0.000). Nevirapine and efavirenz drugs were not detected in any of the collected samples. No ARV residues were detected in water samples (n = 37).ConclusionsThis survey confirms the use of ARVs in animal production in Tanzania as evidenced by the presence of residues in animal feeds. We found lamivudine residues in domestic pigs and broiler chickens at concentrations higher than those recently reported in other East African studies. Farmers living with HIV may be using ARVs from their prescribed medication, which may lead to poor adherence and the emergence of drug resistance. Besides direct human and animal health issues, these residues in animal feeds and animal excreta can lead to environmental contamination leading to several negative impacts. We recommend a total ban on human-designated ARVs in animal production and advocate for comprehensive studies and monitoring systems across African countries to reveal potential societal and other reasons for their use and provide comprehensive solutions using One Health approaches. Publicly Available Content Database